2008
DOI: 10.1016/j.socscimed.2007.11.045
|View full text |Cite
|
Sign up to set email alerts
|

The long-term effects of intimate partner violence on adolescent mothers’ depressive symptoms

Abstract: Adolescent mothers are at high risk of experiencing intimate partner violence (IPV) which may increase their likelihood of depressive symptoms in adulthood, yet little is known about the longterm effects of IPV on adolescent mothers' trajectories of depressive symptoms. The study reported here uses prospective data spanning 14 years from a study of 229 adolescent mothers from Washington State, USA to evaluate the effects of adolescent exposure to IPV on the trajectories of depressive symptoms over time, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 38 publications
3
53
0
Order By: Relevance
“…Couples interact regularly with the health care system during pregnancy and are motivated to make behavioral changes in anticipation of parenthood (Bloch & Parascandola, 2014; Ickovics, Niccolai, Lewis, Kershaw, & Ethier, 2003; Lee et al, 2015). Relationship violence debuts early in teens’ dating experiences and predicts IPV during the adult years (Lindhorst & Oxford, 2008). Interrupting nascent relational patterns that contribute to IPV may prevent a trajectory of relationship violence and interrupt the inter-generational transmission of violence, yielding lasting consequences for individuals, couples, and families (Sutton, Simons, Wickrama, & Futris, 2014; Widom, Czaja, & Dutton, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Couples interact regularly with the health care system during pregnancy and are motivated to make behavioral changes in anticipation of parenthood (Bloch & Parascandola, 2014; Ickovics, Niccolai, Lewis, Kershaw, & Ethier, 2003; Lee et al, 2015). Relationship violence debuts early in teens’ dating experiences and predicts IPV during the adult years (Lindhorst & Oxford, 2008). Interrupting nascent relational patterns that contribute to IPV may prevent a trajectory of relationship violence and interrupt the inter-generational transmission of violence, yielding lasting consequences for individuals, couples, and families (Sutton, Simons, Wickrama, & Futris, 2014; Widom, Czaja, & Dutton, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It is responsible for both women's adverse physical (Ford-Gilboe et al, 2009;Stein & Kennedy, 2001) and mental health (Lindhorst & Oxford, 2008). Studies have demonstrated relationships between IPV and physical injuries (Macy, Giattina, Sangster, Crosby, & Montijo, 2009), homicide (McLaughlin, O'Carroll, & O'Connor, 2012), deliberate self-harm (Jaquier, Hellmuth, & Sullivan, 2013), depression (Huang, Yang, & Omaye, 2011;Taft, Bryant-Davis, Woodward, Tillman, & Torres, 2009), post-traumatic stress disorders (Nixon, Resick, & Nishith, 2004;Peltzer, Pengpid, McFarlane, & Banyini, 2013), suicide thoughts and behaviors (Devries et al, 2011;Gold, Singh, Marcus, & Palladino, 2012) and human immunodeficiency virus (HIV) (El-Bassel, Gilbert, Wu, Go, & Hill, 2005;Sareen, Pagura, & Grant, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, abuse perpetration was associated with increased depressive symptoms for women, not for men. Even if cross-sectional studies cannot establish a causal and temporal relationship between the facts, longitudinal studies show that IPV can lead to depression 56 , as well as precede or facilitate situations of violence 57 . Functional impairment was associated with IPV in two analyzed studies 10,36 , stating that violence may increase vulnerability, leaving the elderly with reduced ability to defend themselves against ill-treatment.…”
Section: Discussionmentioning
confidence: 99%